Responsabilidade social empresarial, suas ações e a produção de mudanças sociais: caso “Prato Popular” - Souza, Luciano e (Universidade do Vale do Rio do Sinos, 2010)
This paper has as objective to research and analyze the project of business social responsibility – “Prato Popular”, which is developed by Gerdau Group, SESI and Prefeitura Municipal de Sapucaia do Sul, in order to show if it is a generator of socio-economic change in its users. It tries also to find out the impressions of those involved in the project, to an evaluation of the project operation related to the speech about social responsibility. It is presented a trajectory concerning the Brazilian social matter, showing the State roles, the new alternatives of organization of the civil society and of the business corporations. This paper also holds a debate about the production or not of socio-economic changes in those people who benefits from the social actions leaded to business social investments which are on suspicion of having a solidarity concern or just economic interest. An empirical research was made in the social project “Prato Popular”, located in Sapucaia do Sul, through an interview to have a sa
Keywords: mudança sócio-econômica; organizações não-governamentais; projetos sociais; responsabilidade social empresarial; non-governmental organizations; social projects; socio-economic change; business social responsibility; Ciências Sociais Aplicadas